Optimalization of Technical and Tactical Training of Greece-Roman Wrestlers - Tashnazarov Djasur Yuldashevich; Nigmatov Ibrokhim Mahmud oglu; Berdiboyev Javlon Ravshan oglu; Rustamov Orif (Genius Publishing Group, 2022)
The article describes how to optimize the training of technical techniques in wrestling. The technique of modeling the teaching of technical techniques in the lessons of wrestling is learned. We used a questionnaire among the trainers on how to use the training process modeling methods.
Keywords: Physical training; technical methods; training; modeling